2010
DOI: 10.1002/bdra.20734
|View full text |Cite
|
Sign up to set email alerts
|

Preconception care for women with diabetes and prevention of major congenital malformations

Abstract: This article provides an overview of the rationale for diabetes preconception care interventions for women with diabetes and the efficacy in reducing the excess occurrence of major congenital malformations. The problems with broad use of individualized preconception care are considered. In addition, suggestions are made for the implementation of more comprehensive interventions in the community and usual diabetes care settings, to address the multiple ongoing challenges in the prevention of structural anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(38 citation statements)
references
References 235 publications
(316 reference statements)
0
37
0
1
Order By: Relevance
“…While no study has directly linked levels of maternal HG in the first trimester when the heart develops with the risk of CHD, lower maternal glycosylated hemoglobin levels (hemoglobin A 1c ), which serve as an indicator of HG over the preceding 2-3 months, have been shown to be associated with a reduced risk of birth malformations in humans (70)(71)(72). It was recently reported that diabetes-induced elevation of maternal blood glucose levels during the 15th-18th week of gestation were correlated with CHD in a California-based case-control study (73).…”
Section: Discussionmentioning
confidence: 99%
“…While no study has directly linked levels of maternal HG in the first trimester when the heart develops with the risk of CHD, lower maternal glycosylated hemoglobin levels (hemoglobin A 1c ), which serve as an indicator of HG over the preceding 2-3 months, have been shown to be associated with a reduced risk of birth malformations in humans (70)(71)(72). It was recently reported that diabetes-induced elevation of maternal blood glucose levels during the 15th-18th week of gestation were correlated with CHD in a California-based case-control study (73).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] The associations observed between maternal pregestational diabetes mellitus and CHDs are strong (ie, relative risk estimates of ≥4) and evident for type 1 and type 2 diabetes mellitus. 18,20,[22][23][24] Furthermore, the risks of CHDs and other birth defects are known to increase among the offspring of women with diabetes mellitus who have poorer metabolic control 25 and to be attenuated among the offspring of women with pregestational diabetes mellitus who are enrolled in preconception care programs focused on management of pregestational diabetes mellitus. 26,27 Although the underlying mechanisms for the association of diabetes mellitus with CHDs and other birth defects remain unclear, [28][29][30] it is evident that hyperglycemia plays an important role in the development of diabetes mellitus-associated adverse pregnancy outcomes.…”
Section: Article See P 2243mentioning
confidence: 99%
“…Pregnant women with either type 1 diabetes or with T2D essentially show the same risk of CA because maternal hyperglycemia is the key teratogenic factor [30]. However, T2D represents the highest public health concern; its incidence is rising globally, calling for primary prevention strategies based on awareness raising and lifestyle modifications also in emerging economies [31].…”
Section: Tablementioning
confidence: 99%